Tomáš Halík and Holmes Rolston - Post, Stephen, photographer (Colorado State University. Libraries, 2017)
Tomáš Halík, Templeton laureate in 2014, is a Czech priest and philosopher who risked imprisonment for illegally advancing religious and cultural freedoms after the Soviet invasion of his country. Condemned by his nation's communist government as an "enemy of the regime," he organized an underground church that worked for two decades building an extensive secret network of academics, theologians, philosophers and students dedicated to cultivating the intellectual and spiritual underpinnings for the democratic state he and others envisioned. Those years of groundwork and counseling to liberation leaders such as Václav Havel helped Czechoslovakia in transition to democracy following the revolution in 1989.
Keywords: Templeton laureates; Rolston, Holmes, 1932-2025; Halík, Tomáš